Analisis Strategi Pengembangan Wakaf Produktif di Pesantren Al-Ma’tuq Sukabumi - Didik Gelar Permana; Ibdalsyah Ibdalsyah; Rio Erismen Armen (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The lack of optimal management and lack of skills regarding waqf development strategies are often obstacles to the development of productive waqf in Islamic boarding schools. This reason prompted the author to analyze the management of productive waqf in a well-known Islamic boarding school in Sukabumi, namely Al-Ma'tuq Islamic Boarding School. The purpose of this study was to analyze the implementation of productive waqf, opportunities and challenges at Al-Ma'tuq Islamic Boarding School, also to analyze the ideal strategy for the development of productive waqf in Islamic boarding schools. The research method used is a qualitative method with a field study approach. The techniques used in data collection are observation, interviews, and documentation studies. Analysis of the data used is descriptive analysis. After doing the research, the authors found that there are 4 (four) strategies that strongly support the development of productive waqf in Islamic boarding schools. First, the fundraising strategy with the concept of